KEEFEKTIFAN KALIMAT DALAM TEKS LAPORAN HASIL OBSERVASI KARYA SISWA KELAS VII SMP NEGERI 17 PADANG - Setiawan, Muhammad Ichsan; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this research was to describe the effectiveness of the sentence in text of results of observations report of Grade VII students of SMP Negeri 17 Padang. The effectiveness is reviewed based on four indicators, namely (1) right reasoning, (2) right linguistic, (3) right words and terms, and (4) right spelling. This type of research is a qualitative research with descriptive methods. This research was carried out at Padang 17 Public Middle School, which was considered important because it was an attempt to explore and understand the effectiveness of student sentences. The instrument in this study is the researcher himself. The results of this study revealed that the effectiveness of the text sentences from students' observations report can be said to be ineffective, it is 39 or 14% of 281 sentences. Based on the results of research on the effectiveness of the sentence in the text of observation report, it can be concluded into four things. First, students still commit errors in proper reasoning, namely regarding lodic ideas and unity of ideas. Secondly, students still commit errors in proper linguistics, namely regarding (1) placement of elements of syntactic functions correctly, (2) no missing sentence elements, (3) no redundant sentence elements, and (4) parallel sentence elements. Third, students still commit errors in the proper words and terms, namely regarding (1) right concepts, (2) right sense scores, (3) right collocation, and (4) right usage context. Fourth, students still commit errors in correct spelling, namely regarding (1) the use of letters, (2) writing words, and (3) use of punctuation .Â Kata kunci:Â Keefektifan Kalimat, Teks Laporan Hasil Observasi